A Single 2‐(2′‐Hydroxyphenyl)benzothiazole Derivative Can Achieve Pure White‐Light Emission. Issue 11 (4th September 2014) - Cheng, Jinling; Liu, Di; Bao, Lijun; Xu, Kai; Yang, Yang; Han, Keli
Abstract The synthesis and photophysics of two novel 2‐(2′‐hydroxyphenyl)benzothiazole (HBT) derivatives are presented. The electron‐withdrawing trifluoromethyl (CF3) group in compound 1 facilitates the deprotonation of the phenolic hydroxy group. Well‐resolved triple fluorescence from the enol, keto, and phenolic anion, which ranges from 350 to 600 nm, was detected for 1 in ethanol, which marks the first time triple fluorescence from an excited‐state intramolecular proton transfer (ESIPT) molecule has been reported. Both triphenylamine and CF3 were introduced into derivative 2. Intramolecular charge transfer and the "red‐edge effect" resulted in the bathochromic shift of dual fluorescence of 2. Triple fluorescence was also observed for 2 in ethanol. In mixed acetonitrile and ethanol, pure white‐light emission with CIE coordinates of (0.33, 0.33) and a quantum yield of 0.25 was achieved for 2. This work provides a new avenue for the rational design of an ESIPT molecule to achieve white‐light generation under mild conditions.